The Character of Thurston’s Circle Packings with Obtuse Exterior Intersection Angles (Analysis in Theory and Applications, 2025)
We study the character of Thurston's circle packings with obtuse exteriorintersection angles, and we get some simple criteria for the existence of hyperboliccircle packings. Moreover, the compactness theorem of combinatorial Ricci flows inhyperbolic background geometry with the weight function $Φ ∈ [0, π)$ is obtained.As a consequence, We generalize G. Lin's result [12] from acute exterior intersectionangles case to obtuse exterior intersection angles case.
Keywords: Character; Thurston’s circle packing; combinatorial Ricci flow; obtuse exterior intersection angles.